Functional Outcomes after Bilateral Hand Transplantation: A 3.5-Year Comprehensive Follow-Up. Issue 1 (January 2016) - Singh, Mansher; Sisk, Geoffroy; Carty, Matthew; Sampson, Christian; Blazar, Philip; Dyer, George; Earp, Brandon; Pribaz, Julian; Pomahac, Bohdan; Talbot, Simon G.
Abstract : Background: Since the first successful hand transplantation in 1998, 72 patients have been operated on for unilateral/bilateral hand transplantation across 13 countries. There have been multiple studies evaluating the outcomes of hand transplantation; however, there is considerable variability among the outcome measures evaluated in these studies. Methods: This article reports functional outcomes in a patient with bilateral hand transplants at a mid-forearm level with serial follow-ups over 3.5 years. Different parameters used to study the functional outcomes include the Disabilities of the Arm, Shoulder, and Hand score, the Carroll test, the Hand Transplant Score System, the Short Form-36 Health Survey, and routine occupational therapy measures. Various task-oriented outcomes were also assigned to provide milestones to the recovery. Results: The patient had a Disabilities of the Arm, Shoulder, and Hand score of 40, a Carroll test score of 48 (right) and 49 (left), and a Hand Transplant Score System score of 58 (right) and 57.5 (left) at 3.5-year follow-up. Interestingly, his objective scores did not change significantly during the follow-up, but he continued to function quite independently and is subjectively pleased with his outcomes. Conclusions: Multiple functional outcome measures provide an objective way to follow patients who have undergone hand transplantation. The authors propose a series of measures to elucidate subtleties in functional gains. However, use of this series in isolation may belie subjectively good results. They also propose a series of milestones in the recovery to give a better real-world explanation of progress. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, V.